Peran Penting Bauran Pemasaran (Marketing Mix) Terhadap Peningkatan Penjualan Outlet Makbule - Tesar Buri Anggara; Sofyan Lazuardi (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
In the increasingly fierce world business competition, it causes business people to think about developing their business. Many are unstable and the competition is getting tougher, so we as business people make strategies so that their business is superior. In the business world, a condition that is difficult to maintain is to keep customers in order to always consume the product or it can be called customer loyalty. To create customer loyalty, we as entrepreneurs really need a marketing strategy to market our products. Establish a marketing strategy that can support in marketing our products to create customer loyalty by using a marketing mix strategy consisting of product, price, place, promotion. Sellers who provide product satisfaction to customers, customers will be generous. If there is customer loyalty, it will have an effect on increasing sales